PENERAPAN BIMBINGAN KELOMPOK DENGAN TEKNIK REBT UNTUK MENINGKATKAN MOTIVASI BERPRESTASI SISWA DI MTS - Vesti Dwi Cahyaningrum; Olivia Dwi Cahyani; Elis Ni’matur Rohmah (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2017)
Achievement Motivation itsimportant student must have as an encouragement to achieve in the future, so it needs the right to increase student achievement motivation. The purpose of this study to determine the increase in achievement motivation through group guidance services with REBT (Rational Emotive Behavior Therapy) to the students MTS Biatulmuttaqin Tumbrasanom. The method used in this study with a design method of pre-eksperimen, one group pretest-posttest design. Subjects in the study of five students with low achievement motivation. Data collection techniques in this study using a scale of achievement motivation. The results showed that students' achievement motivation can be enhanced by using group guidance services, as evidenced by the results of the data analysis of achievement motivation as pre-test and post test scores obtained Asymp.sig.(2-tailed) 0,043. Because 0,043 its small of 0,05 (Rhitung< Rtabel), then Ho is rejected and Ha accepted, it means there is an increase in achievement motivation before and after a given group counseling services to students MTS Biatulmuttaqin Tumbrasanom. The conclusion in this study is an increase in achievement motivation between before given guidance services group after group counseling services provided to the students MTS Biatulmuttaqin Tumbrasanom. This means that achievement motivation can be enhanced through group guidanceservices with REBT (Rational Emotive Behavior Therapy).